Carmina Latina epigraphica musiva et depicta non Buecheleriana nec Zarkeriana. I (Minerva, 2019)
The aim of this paper is to complete a research which tends to study all the carmina latina epigraphica of the Roman Republic and Empire, written over mosaic pavements or depicted. Our first two papers published in this field («CLE Musiva et Depicta Buecheleriana», Habis 21 1990 173-203 and «CLE Musiva et Depicta Zarkeriana», Faventia 12/13 1990-1991 369-384) have studied the CLE musiva et depicta contained in the collections of Bücheler-Lommatzsch and of Zarker. This paper and, perhaps, another one which will complete him, revise all the new matherial knew from 1958 (date of publication of Zarker's monography) to 1992 and the old matherial forgotten by Bücheler-Lommatszsch or Zarker.